2009
DOI: 10.1387/ijdb.072507sr
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Prrxl1 alternative splice variant during the development of the mouse nociceptive system

Abstract: Background Gene expression can be differentially regulated by alternatively spliced transcription factors, providing a mechanism for precise control of diverse morphogenetic events. The paired-type homedomain transcription factor Prrxl1 (formerly known as Drg11) was described as a key regulator of the differentiation of the spinal cord neuronal circuit dedicated to the processing of nociceptive information. Here, we report the characterization of a Prrxl1 alternative splice variant that we termed Prrxl1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 22 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…As any Prrxl1 co-regulators or co-factors are presently unknown, we cannot distinguish between these two possibilities. We have previously shown that Prrxl1 is the most expressed isoform in developing DRG and dorsal SC [21]. The expression ratio between Prrxl1 and Prrxl1b is kept constant in the DRG, but varies in the dorsal SC during later embryonic and postnatal development [21].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As any Prrxl1 co-regulators or co-factors are presently unknown, we cannot distinguish between these two possibilities. We have previously shown that Prrxl1 is the most expressed isoform in developing DRG and dorsal SC [21]. The expression ratio between Prrxl1 and Prrxl1b is kept constant in the DRG, but varies in the dorsal SC during later embryonic and postnatal development [21].…”
Section: Discussionmentioning
confidence: 97%
“…We have previously shown that Prrxl1 is the most expressed isoform in developing DRG and dorsal SC [21]. The expression ratio between Prrxl1 and Prrxl1b is kept constant in the DRG, but varies in the dorsal SC during later embryonic and postnatal development [21]. Transcriptional autorepression may thus control the expression ratio of Prrxl1 isoforms, being Prrxl1b more effectively repressed than Prrxl1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Prrxl1 mRNA sequence described by these authors contained the start codon in exon 2, whereas exon 1 corresponded to a 5Ј-UTR. More recently, by the use of 5Ј-rapid amplification of cDNA ends assays with mice spinal cord RNA extracts, we described two novel variants of Prrxl1 containing alternative exon 1 that gives rise to distinct 5Ј-UTRs (11). BLAST searches of GenBank TM database led us to identify sequences that correspond to all the three 5Ј-UTRs that contained both the first and the last coding exons of the annotated Prrxl1.…”
Section: Prrxl1 5ј-utr Variants Present Distinct Mrna Stability Andmentioning
confidence: 99%
“…Recently, a Prrxl1 alternative spliced variant was identified, and multiple variants of exon 1 in both Prrxl1 mRNA isoform sequences were discovered, suggesting the existence of various 5Ј-untranslated regions (5Ј-UTRs) controlled by distinct promoters (11). Modulation of gene expression through alternative promoter usage is now widely accepted following evidence gathered in the past years (12,13).…”
mentioning
confidence: 99%